Comparative Study Morphology on Genital Tract between Local Iraqi Hen and Duck. (Journal of the College of Basic Education, 2022)
This study was carried out to compare the morphological structures of ovary and oviductal regions of the apparently healthy immature and mature female laying hens (Gallus gallus domesticus) and ducks (Ansa ansa domesticus ),.for this purpose the age of birds taken at average 16 weeks for immature with weight average 700 gm and 48-52 weeks and weight 1700 gm for mature birds. All of the morphometrical parameters were taken after euthanasia , the ovary and oviduct weight , length as well as width of them were recorded. Our analyses indicated that the mean weigth , length as well as width of the five regions of the oviduct in mature hen were significantly differences (p˂0.01) greater than in duck. Moreover, noticed that increase from immature parameters to mature ages in hens and duck, but in hens parameters the increases was higher significant (p˂0.01) in most parameters.